Pengaruh Sosial Budaya Dan Geografis Terhadap Perilaku Merokok Pada Lansia Perempuan Di Wilayah Dataran Tinggi Dieng Wonosobo - Widiyaningsih, Dwi; Suharyanta, Dwi (STIKES Yayasan RS.Dr.Soetomo, 2020)
All forms of charm of the dieng region are able to attract the attention of both domestic people and abroad, with its unique socio-cultural and geographical location which is approximately 2000m above sea level with temperatures reaching 5 degrees Celsius at night and 10 degrees Celsius during the day. It turned out to be a very beautiful natural condition not accompanied by proper healthy behavior, 9 out of 10 households smoke to eliminate the cold, and 4 out of 6 elderly women smoke because of the culture of their ancestors who descended as a cultural heritage signifying that they are strong and respected women. culture like this is certainly very in contrast to the GERMAS (Healthy Community Movement) non-smoking program which was launched in 2016 as an increase in ARI cases from 2009 until 2104 and tends to be stagnant until 2017, as well as various disease events due to smoking such as pulmonary TB, cancer, etc. are also often found in the district Wonosobo. This study aims to look for socio-cultural and geographical influences on smoking behavior in the elderly female sex in the Dieng plateau region wonosobo district. The subjects of this study were elderly women people over 60 who smoke. with a population of 113 elderly, technical. The sample used is total sampling. This type of research is quantitative with cross sectional design as for the analysis of the data used is bivariate analysis (kendall’s tau) where the results are obtained there is a significant influence between social culture on smoking behavior in elderly women (0.001 <0.010), and there is an influence geographic significance of smoking behavior among elderly women (0,000 <0.010). With a significance level of 0,000 (ρ <0.05) so it can be concluded socially culture and geography are related to the smoking behavior of women in the highlands dieng.